TRATKUL Solusi Cerdas Pakan Alternatif Peningkat Kualitas dan Kuantitas Telur Itik - Nugraeni, Utami; Rahmawati, Kurnia; Febrina TUE, Risfi; Diyanah, Siti Mustamatud; Saha, Muhammad Agni (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Conch field / kakul a rice crop pest found in many parts of Indonesia, especially the paddy Cilacap. Keong more widely known as pests, in addition to the rice snail belonged to a water snail intermediate host Fasciola sp, the flatworm species that attacks the liver rather the duct biliverus ruminants (cattle, sheep, goats) However, paddy snails actually have very good nutrition if used properly, for example by providing rice field snails to ducks as an adjunct feed. With fairly high protein content, giving the rice field snails can provide addition of muscle mass, as well as an increase in reproductive hormones that will stimulate the improvement in quantity and quality of duct eggs. Contains nutrients intact with snail snail paddy rice has been processed to have differences. Conch rice has been processed to have a higher protein content. With so many complaints from farmers on rice field snails as well as opportunities for the utilization of plant pests such as duck feed rice in Indonesia, particularly in the Cilacap region is quite high, so we are motivated to make a PKM-K with the title